Effect of longitudinal reinforcement on the soundless chemical demolition degree of reinforced concrete columns. (13th August 2022) - Li, Ruisen; Zheng, Wenzhong; Tian, Weichen; Yan, Yu; Li, Guangchao
Abstract: Soundless chemical demolition has great potential for application in the field of building demolition in densely built areas. However, the application of this method was limited due to less guidance can be applied to reinforced concrete. Thus, this study investigated the effect of longitudinal reinforcement on the crushing degree of concrete columns. Experimental results showed that the number of steel bars had a greater impact on the development of crack width than diameter. Moreover, the longitudinal reinforcement had a greater impact on the transverse cracks than other types of cracks. This study introduced fractal dimension and characteristic value of specimen to describe the overall crushing degree and reinforcement arrangement of the specimens, respectively. The fractal dimension increased with an increase in the characteristic value. This study explored the influence of longitudinal reinforcement on the crushing degree of concrete columns, which laid the foundation for soundless chemical demolition of buildings in densely built areas.